Design and testing performance of a magneto-rheological elastomer isolator for a scaled bridge system. (January 2018) - Li, Rui; Mu, Wenjun; Zhang, Luyang; Wang, Xiaojie
In this article, we proposed a study on the performance of a magneto-rheological elastomer isolator for the vibration isolation of a scaled bridge system. Based on dimensionless analysis of dynamic characteristics of real bridge system, the vibration acceleration and displacement of bridge deck are considered as evaluation indexes. According to the parameters of a scale model for the three-span bridge, a scaled magneto-rheological elastomer isolator prototype is designed and manufactured, and a small-scale test bench is set up to test the performance of magneto-rheological elastomer device for bridge vibration control. The experimental study shows that the bench testing results are consistent with that of theoretical model in terms of the vibration displacement and acceleration. Therefore, the small-scale study of bridge vibration system with magneto-rheological elastomer isolator based on similarity theory reveals the performance of a real bridge system. It shows that the scaled platform can model the vibration performance of a three-span bridge, which provides a fundamental understanding of the MRE isolator in the applications for the full-scale bridge system.